Film hieroglyphs : ruptures in classical cinema - Conley, Tom (University of Minnesota Press, 2006)
At a time when traditional film theory privileged the purely visual, Film Hieroglyphs introduced a new way of watching film-examining the ways in which writing bears on cinema. Author Tom Conley gives special consideration to the points (ruptures) at which story, image, and writing appear to be at odds with one another. Conley hypothesizes that major directors-Renoir, Lang, Walsh, Rossellini-tend unconsciously to meld history and ideology. Graphic elements are seen as simultaneously foreign and integral to the field of the image. From these contradictions hieroglyphs emerge that mark a design.